Decreased Expression of Semaphorin 3A and Semaphorin 7A Levels and Its Association with Systemic Lupus Erythematosus. (17th February 2020) - Wang, Peng; Mao, Yan-Mei; Liu, Li-Na; Zhao, Chan-Na; Li, Xiao-Mei; Pan, Hai-Feng
ABSTRACT: A growing body of data suggests that semaphorins are involved in both normal and pathological immune responses, as well as autoimmune pathologies. To investigate the plasma semaphorin 3A (Sema3A) and semaphorin 7A (Sema7A) levels in systemic lupus erythematosus (SLE) patients and their correlation with clinical manifestations and laboratory indexes, a two-step method was applied. First, 80 SLE patients and 80 healthy controls were recruited for comparing serum Sema3A and Sema7A concentrations. Second, 40 rheumatoid arthritis (RA) patients and 40 sjögren's syndrome (SS) patients were then included as disease controls. Plasma Sema3A and Sema7A concentrations were detected by ELISA. There were significant differences in Sema3A and Sema7A among four groups. When compared to healthy controls, both Sema3A and Sema7A levels were decreased in SLE and increased in RA; increased Sema3A level and decreased Sema7A level were found in SS. There were significant differences in Sema3A concentration between SLE and RA, SLE and SS. Moreover, there were significant differences in Sema7A level between SLE and RA, SS and RA. However, no significant differences in Sema3A between SS and RA and no significant differences in Sema7A between SS and SLE were observed. Both plasma Sema3A and Sema7A levels were correlated with anti-SSA and IgM. Area under curve (AUC) of the receiver operating characteristic (ROC) curve for Sema3A and Sema7A were 0.535 (0.455–0.613) and 0.671 (0.594–0.742), respectively. Aberrant Sema3A and Sema7A expression and their clinical associations in SLE suggest their important role in this disease.